Cognition in Organisations: What it Is and how it Works. Issue 2 (22nd December 2020) - Secchi, Davide; Cowley, Stephen J.
Abstract : Drawing on contemporary work that traces cognition to embodiment, we present a model of cognition in organisations. In so doing, we add a middle ground to previous models: far from opposing macro to micro, we focus on how the meso influences complex adaptive dynamics. Taking peer‐review as an exemplar, we show that organisational needs can be fulfilled by orchestrated coordination. Constrained by brains and bodies (the micro domain) that attune to structural constraints (the macro domain), human beings use material culture – artefacts, language, practices, etc. – to animate what we call social organising in the meso domain. The resulting coordination can anticipate organisational goals such that, as demonstrated in the case of peer‐review, social organising regulates epistemic practice. Flexible, embodied activity enables reviewers and to meet the aims of organised science by pooling the expertise of those involved. They use multi‐scalar dynamics that are mediated by material, temporal and spatial resources that, when concerted, constrain and enable organisational cognition.